Efeito do contraíon Cl- no arranjo supramolecular da Fenilefrina - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
Phenylephrine is widely used as a nasal and mydriatic decongestant in various nasal and ophthalmic formulations. Phenylephrine is traditionally commercialized in its saline form as phenylephrine hydrochloride. Due to changes in crystalline packing, counterion inclusion affects the chemical, physical, biological properties, and reactivity. Structural, topological, and energy analyses are essential to compare and understand those changes in physicochemical properties and their impacts on drug production. This study evaluates the conformational changes, crystalline packaging, and interactions of phenylephrine and phenylephrine hydrochloride. Theoretical calculations were carried out to assess the stability and supramolecular arrangement. The energetic gap ΔELUMO-HOMO shows that the Cl- counterion provides greater stability for phenylephrine. Phenylephrine exhibits a more significant number of interactions O···O and O···H that increase hygroscopicity and chemical reactivity of a compound. The presence of the counterion alters the conformational and structural properties of phenylephrine, causing changes in its properties and influencing its use.
Chlorine counterion effect into the supramolecular arrangement of Phenylephrine
Keywords: Fenilefrina; Contraíon Cl-; M06-2X/6-311++G(d,p); Superfície de Hirshfeld; QTAIM; Phenylephrine; Counterion Cl-; M06-2X/6- 311++G(d,p); Hirshfeld surface; QTAIM; CIENCIAS EXATAS E DA TERRA::QUIMICA